Ectomycorrhizal and Dark Septate Fungal Associations of Pinyon Pine Are Differentially Affected by Experimental Drought and Warming - Gehring, Catherine; Sevanto, Sanna; Patterson, Adair; Ulrich, Danielle E. M.; Kuske, Cheryl R. (Frontiers in Plant Science, 2020)
Changing climates can cause shifts in temperature and precipitation, resulting in warming and drought in some regions. Although each of these factors has been shown to detrimentally affect forest ecosystems worldwide, information on the impacts of the combined effects of warming and drought is lacking. Forest trees rely on mutualistic root-associated fungi that contribute significantly to plant health and protection against climate stresses. We used a six-year, ecosystem-scale temperature and precipitation manipulation experiment targeted to simulate the climate in 2100 in the Southwestern US to quantify the effects of drought, warming and combined drought and warming on the root colonization (abundance), species composition and diversity of ectomycorrhizal fungi and dark septate fungal endophytes in a widespread woodland tree, pinyon pine (Pinus edulis). Our results show that pinyon shoot growth after six years of these treatments was reduced more by drought than warming. The combined drought and warming treatment reduced the abundance and diversity of ectomycorrhizal fungi more than either treatment alone. Individual ectomycorrhizal fungal taxa, including the drought tolerant Cenococcum geophilum, were present in all treatments but the combined drought and warming treatment. The combined drought and warming treatment also reduced the abundance of dark septate endophytes, but did not affect their diversity or species composition. The current year shoot growth of the trees correlated positively with ectomycorrhizal fungal diversity, highlighting the importance of diversity in mutualistic relationships to plant growth. Our results suggest that ectomycorrhizal fungi are more important than dark septate endophytes to growth in P. edulis, but also more susceptible to the negative effects of combined climate stressors.